THE PURCHASE DECISION OF HALAL LABELED PRODUCTS BASED ON BRAND AWARENESS AND BRAND IMAGE FOR BUGIS-MAKASSAR CONSUMERS IN MAKASSAR CITY - Kasnaeny Karim; Muhammad Jibril Tajibu (Hasanuddin Economics and Business Review, 2022)
Competition between products is currently very tight accompanied by the emergence of new brands that are able to attract attention, so that consumers have many choices in deciding which product to buy. The condition of the city of Makassar with a predominantly Muslim population will definitely consume halal products, amidst the rise of products from abroad. Thus, this study aims to find out how the ability of brand awareness and brand image influences consumer decisions to buy halal products for consumers of Bugis-Makassar ethnicity in Makassar City. To solve the research problem, a questionnaire was distributed to selected respondents through a purposive sampling technique totaling 100 people representing 25 respondents from the city of North Makassar, 25 respondents to East Makassar, 25 respondents to West Makassar and 25 respondents to South Makassar with Bugis-Makassar ethnic criteria. Data analysis used in this study is parametric statistical analysis using multiple linear regression. The results of this study indicate that brand awareness and brand image have a positive and significant effect on purchasing decisions for products labeled halal in the Bugis-Makassar community. Simultaneously brand awareness and brand image have a significant effect on the decision to purchase halal products. While the R value is 51.9%. which means the decision to purchase halal products is strongly influenced by brand awareness and brand image variables.